The Engagement-Trust Paradox: A Qualitative Analysis of Baho Gamira’s TikTok Content Among University Students: - Jacqueline Laoli; Afore Tahir Harefa; Neni Suryani Gulo; Sharley Grace Mendrofa (Raja Zulkarnain Education Foundation, 2026)
This study investigates students' perceptions of promotional content for Baho Gamira Recreational Tourism on TikTok, focusing on the integration of animated storytelling in tourism marketing. Utilizing a qualitative descriptive approach, data were collected through semi-structured interviews and online surveys involving 30 students to analyze the influence of visual narrativity and perceived authenticity on travel intentions. The findings identify a significant